Response of different sowing dates on seed protein content and productiviQ of chickpea (Cicer arietirzum) genotgrpes* - SINGH, TEJ PAL; DESMMUKH, P S; KUSHWAHA, S R (The Indian Journal of Agricultural Sciences, 2011)
A field experiment was conducted during 2002-03 with 6 chickpea genotypes including, 3 released varieties, viz 'Pusa 256; "Pusa 372', 'BGD 72' and 3 advance lines, vk 'DG 36', 'DG 46', and 'DG 51' under different planting dates : normal (15 November), late (30 Nov.) and very late (1 5 December) were grown . The seed yield and seed protein content were significantly higher in late sowing, higher percentage of protein (25.55%) was recorded in late planting followed by very late (24.85%) and normal (23.83%) plantings. Among the genotypes DG 46' and 'DG 5 1 ' showed higher mean values of protein content, ie 25.88 and 25.05% respectively. In general advance breeding lines showed hgher mean values of protein content in comparison to the released varieties. The higher seed yield was recorded when plants were grown in late planting with 10 % more yield than normal and 22 %higher than very late planting. On the basis of data of heat-use efficiency advance line 'DG 36' was found superior as compared to other advance lines and released genotypes, so such material may be included in breeding programme to improve these desirable traits.